Isolasi dan Karakterisasi Enzim Selulase Cairan Rumen Sapi untuk Hidrolisis Biomassa - Heri Setyoko; Budi Utami (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2016)
The purposes of this study are: 1) knowing the isolation procedure cellulase enzymes contained in cow rumen fluid. 2) observing characterization of cellulase enzymes isolated from cow’s liquid rumen with variables pH, temperature, and incubation time. 3) exploring glucose from the enzymatic hydrolysis of cellulose biomass on rice straw, sugarcane bagasse, rice husks, paper, and corncobs. Isolation of the enzyme was observed by employing several stages, they are dialysis stage 1, centrifugation stage 1, the purification of enzymes 40%, centrifugation stage 2, and dialysis stage 2. Glucose test results obtained by the method nelson samogyi. The specific activity of the enzyme obtained divided by the enzyme activity of cellulase enzyme protein content. Protein assay reagent used with Lowry. From this study it can be concluded that: 1). Cellulase enzymes can be obtained from the isolation of the enzyme with cellulase enzyme-making stage of the cow's rumen, dialysis stage 1, centrifugation stage 1, the purification of enzymes, centrifugation and dialysis stage 2. 2) Characterization of cellulase enzymes isolated from cow’s liquid rumen obtained pH optimum at pH 5.4 with the activity of the enzyme 311.64 µmol/ml and the specific activity of the enzyme 11.06 µmol/mg. The optimum temperature obtained maximum activity at a temperature of 39oC with the activity of the enzyme 306.35 µmol/ml and a specific activity of enzyme of 10.87 µmol/mg. The maximum incubation time of maximum activity was obtained at 60 minutes of incubation time with enzyme activity 292.90 µmol/ml and the specific activity of the enzyme 10,39 µmol/mg. 3). Test glucose levels in rice straw biomass was obtained with glucose levels 207.25 mg/ml. Sugarcane bagasse with glucose levels 193.64 mg/ml. Rice husk with glucose levels 202.96 mg/ml. Paper with glucose levels 197.64 mg/ml. Corncobs with glucose levels 230.77 mg/ml.Keywords: Cellulase enzymes, pH, Temperature, Time